The effect of information technology devices on student learning outcomes: a systematic literature review - Edy Sasmito; Garianto; Sutrisni Andayani (Indonesian Institute For Counseling, Education and Therapy, 2026)
Objective of this study is to systematically synthesize empirical evidence on the effect of Information Technology (IT) devices on student learning outcomes and to identify multi-level factors that moderate this relationship, guided by the Technological Pedagogical Content Knowledge (TPACK) framework, Cognitive Load Theory (CLT), and Self-Determination Theory (SDT). Method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Literature searches were conducted in Google Scholar, Scopus, and ERIC databases using Boolean search strings: (